Inhibition Activity of Garlic (Allium sativum) Skin Aqueous Extract on Mastitis Causing Microorganisms - Syamsi, Afduha Nurus; Pratiwi, Meyta; Nugroho, Aras Prasetiyo (ANIMAL PRODUCTION, 2019)
The study was aimed to identify the effectiveness of the inhibitory activity of garlic skin extract (GSE) with different concentrations on the growth of Staphylococcus aureus, Streptococcus mutants, Escherichia coli, and Candida albicans. The study used the Kirby-Bauer method in a completely randomized (CRD) design with five treatments (positive control, negative control, 5% GSE, 10% GSE, and 15% GSE) and three replicates. The extract was obtained through evaporation of garlic skin macerated with aquadest solvent. The data were subjected to ANOVA, continued with an Honestly Significant Difference (HSD) test. The results showed that GSE concentration (minimum 5-10%) was highly significant to inhibit the growth of mastitis-causing microorganisms.